THE ORIENT ENCHANTMENT DALAM KEBIJAKAN AUSTRALIA IN THE ASIAN CENTURY - Winadi, Guguh (Global and Policy Journal of International Relations, 2014)
ABSTRACTThis research explain the change of Australian’s foreign policy toward to the East. Australia as a country that previously close to the West, now show the intensity to the East. East region with an exotic market grew through the long process of economic and political modernization in the region. The process of modernization in Asia or Asian revival process has brought the region to the East became the center of the new economy in the world, which in the last two decades have shown a very impressive economic growth. This led to change trend in the global constellations that previously was dominatied by the Western countries. However, the dominance of the Western economy down since the onset of the financial crisis in 2008, this crisis is a sign of the start of the era of eastern oriented in the international world. This Trend has affected Australia to make foreign policy a more eastern oriented. The promulgation of the policy of Australia In The Asian Century is a form of foreign policy trend of Australia with oriental themes, which are intended to respond to the Asian economy era in 13 yearsKeywords: rise of Asia, 2008 global crisis, foreign policy trend, Eastern Oriented,economic cooperation.DOI:https://doi.org/10.33005/jgp.v2i01.1981